Hubungan Antara Kontrol Diri dengan Perilaku Melanggar Peraturan pada Santri Pondok Pesantren X di Kabupaten Sleman - Romadhon .; Indra Wahyudi; Eny Rohyati (LPPM Universitas Proklamasi 45, 2019)
Self-control is forms the ability to regulate, guide, and regulate functions that can bring individuals in a positive direction. Self-control will control santri do not things that are’t neededby santri, because it’s contrarythe norms prevailing inthe pesantren.The purpose of this study is to prove the relationship between self-controlwithbreaking the rulesbehaviorby the santri.The benefits of this research are input for caregivers and boarding school administrators in educating and taking care of the santri.The dependent variable of this study isbreaking the rulesbehavior, while the independent variable is self control. The hypothesis of this study isa negative relationship between self-control andbreaking the rules behavior inthe pesantren.The higherlevel of self controlthen lower the behavior breaking the rules.Hypothesis testing with product moment correlation shows the result (rxy) -0.054 with p = 0.750 (p> 0.05). The result meaningis no relationship between the self-controlvariable with the behavior breaking the rules variable at Pondok Pesantren X in Sleman Regency. This means that the hypothesisforward by the researcher is rejected.Keywords: Self-Control,Breaking the rulesbehavior, Santri Pondok Pesantren X.Abdurrohman, W. (1995). pesantren sebagai subkultur. Dalam M. D. Rahardjo (Ed.).Pesantren dan pembaharuan. Jakarta: LP3ES. Arnett, J. (1995). The young and the reckless: Adolescent reckless behavior. Current Direction Psychological Science. 4(3), 67-71. Averill, J. R. (1973). Personal control over aversive stimuli and it’s relationship to stress. Psychological Bulletin. 88: 286-303. Azwar, S. (1999). Penyusunan skala psikologi. Ed. Ke-2.Yogyakarta: Pustaka Pelajar. Chaplin, J. P. (2006). Kamus lengkap psikologi. Jakarta: Raja Granfindo Persada. Ghufron, N. M. & Risnawati, R. (2010). Teori-teori psikologi. Yogyakarta: Ar-Ruz Media. Hurlock, E. B. (1999). Adolescent development. Tokyo: McGraw-Hill Kogakusha. Ltd. Kartono, K. (2003). Patologi sosial: Kenakalan Remaja. Jilid 2.Jakarta: PT Raja Grafindo Persada Kazdin, (1998). Psikologi sosial. Jakarta: Erlangga. Lauster, P. (1978. The personality test. London: Pan Books, Ltd. Lazarus, R. S. (1991). Pattern of adjustment. Tokyo: McGraw-Hill Kogakusha. Ltd. Masyhud, M. & Khusnudilo, M. (2003). Manajemen pondok pesantren. Jakarta: Diva Pustaka. Messina. (2003). Developing self-control. Tokyo: McGraw-Hill Kogakusha. Ltd. Muhajir, Hermanto, & Wahyuni. (2013). Peran pondok pesantren dalam mengatasi kenakalan remaja, jurnal Psikologi. 1-18. Nataatmaja, S. (1998). Pengantar pendidikan kesehatan dan ilmu perilaku kesehatan. Yogayakrta: Penerbit Andi Offset.Santrock, J. W. (2003). Perkembangan masa hidup. Jilid 1 (Penterjemah: A. Chusaini). Jakarta: Penerbit Erlangga. Sekaran, U. (2003). Teknik penyusunan skripsi. Jakarta: Pustaka Jaya. Singgih, D. G. (2006). Dari anak sampai usia lanjut. Jakarta: Gunung Mulia. Zhang, Z. & Avery, R. D. (2009). Rule breaking in adolescence and entrepreneurial status: An empirical investigation. Journal of Business Venturing. 24, 436–447.